Post-Partition Citizenship Policies: Lessons from Post-Yugoslav Federal States. - Džankić, Jelena; Keil, Soeren (Publius: The Journal of Federalism)
Citizenship policies are important tools of inclusion and exclusion in a post-partition context. In most cases, they reflect the unitary and mono-ethnic character of newly established states. Their function in countries and territories where an ethnonational break-up resulted in further ethnically diverse societies is far more complex. Citizenship in multilevel states created through state disintegration is a counterintuitive combination of (1) the legacies of the old citizenship tradition and replications of the old federal structure, and (2) processes of ethnic engineering and designing group-centric citizenship regimes. Legacies of the old structure are framed by the modalities of break-up and initial determination of citizenry (e.g. the absence of zero solution), but strongly mirror elements of the previous multilevel construction of citizenship, including bottom-up derivation, ethno-national determination of membership, voting rights and representation. Discontinuities in citizenship policies reflect wider tensions between nation- and state-building (and destruction), and how these processes have been molded through different international influences. We undertake a case-study of two post-Yugoslav multilevel states, Bosnia and Herzegovina and the Federal Republic of Yugoslavia/the State Union of Serbia and Montenegro, with the intent of drawing broader conclusions on how citizenship policies can keep states together or break them apart.